Assessment of clinically relevant drugs as feline P-glycoprotein substrates - Mealey, Katrina L.; Burke, Neal S. (Frontiers in Veterinary Science, 2025)
IntroductionThe drug transporter P-glycoprotein (P-gp) influences drug disposition by playing key roles in limiting brain penetration and enhancing biliary excretion of substrate drugs. Guidance documents from U.S. and European regulatory agencies recommend that manufacturers determine the P-gp substrate status of new medications intended for human patients. The rationale is that P-glycoprotein-mediated drug–drug interactions may cause serious adverse drug events. Unfortunately, the same regulatory guidance does not encompass new feline drugs even though a P-gp knockout mutation (ABCB11930_1931del TC) is present in a subpopulation of cats. Recent reports of a novel macrocyclic lactone, eprinomectin, causing neurological toxicosis in cats homozygous for ABCB11930_1931del TC, imply it is a feline P-gp substrate, but definitive data is lacking, It is intriguing that neurological toxicity has also been reported in a small number of cats treated with amlodipine, capromorelin, and cisapride, however their MDR1 genotypes are unknown.MethodsA competitive efflux assay and feline P-gp expressing cell line were used to assess the P-gp substrate status of thirteen clinically important drugs used in cats.ResultsTen drugs, including eprinomectin, were determined to be substrates for feline P-gp while three drugs were not.DiscussionThis information will help improve drug safety for cats with intrinsic (ABCB11930_1931del TC) and acquired P-gp deficiency. Further, this type of assay may be useful for screening feline drug candidates during the drug approval process.